Maps Roman - Farah, Nuruddin 1945- (Ammann, 1992)
A Somali youth is torn between duty to family and country. On the one hand Askar, an orphan, should look after his foster mother, on the other he wants to be a man and emulate his father who died fighting the Ethiopians. By an English-speaking Somali writer, author of Secrets.
Keywords: Politik; Identity (Psychology) -- Fiction; Orphans -- Somalia -- Fiction; Young men -- Somalia -- Fiction; Somalia -- Politics and government -- Fiction; Fiktionale Darstellung